2014
DOI: 10.1016/j.semcdb.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor, from gene organization to bedside

Abstract: In 1962, epidermal growth factor (EGF) was discovered by Dr. Stanley Cohen while studying nerve growth factor (NGF). It was soon recognized that EGF is the prototypical member of a family of peptide growth factors that activate the EGF receptors, and that the EGF/EGF receptor signaling pathway plays important roles in proliferation, differentiation and migration of a variety of cell types, especially in epithelial cells. After the basic characterization of EGF function in the first decade or so after its disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
137
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 153 publications
(179 reference statements)
0
137
0
2
Order By: Relevance
“…EGF was originally identified by the Nobel laureate Dr. Stanley Cohen and his colleagues as the factor in a submaxillary gland extract that induced precocious eyelid opening and incisor eruption due to stimulation of epidermal growth and keratinization when injected into newborn mice (630). Work by Cohen and Graham Carpenter subsequently identified that EGF's actions were mediated by binding to and activation of EGFR.…”
Section: Introductionmentioning
confidence: 99%
“…EGF was originally identified by the Nobel laureate Dr. Stanley Cohen and his colleagues as the factor in a submaxillary gland extract that induced precocious eyelid opening and incisor eruption due to stimulation of epidermal growth and keratinization when injected into newborn mice (630). Work by Cohen and Graham Carpenter subsequently identified that EGF's actions were mediated by binding to and activation of EGFR.…”
Section: Introductionmentioning
confidence: 99%
“…222 To resolve the problems of in vivo gene delivery, Wolschek et al 223 synthesized PEGylated EGF-containing DNA/PEI complexes for HCC targeting. The study on 2 xenotransplantation models for human HCC showed that expression levels within the tumors were up to 97%-99% of the total transgene expression in vivo, which is two logs higher than levels in the major expressing organ, liver.…”
mentioning
confidence: 99%
“…Growth factors bind to specific receptors which present on cell surface and contain a tyrosine kinase domain in their C-terminus (7,8) .The epidermal growth factor family firmly interfere in implantation process .This family includes epidermal growth factor (EGF), amphiregulin (AR), heparin-binding epidermal growth factor (HB-EGF) and transforming growth factor alpha (TGFα) (9) . At implantation TGFα, HB-EGF and AR are expressed in the uterus; in particular, HB-EGF appears to be highly relevant to implantation.…”
Section: Issn: 2320-5407mentioning
confidence: 99%